Physiological effects of 100PLUS(TM) chilled drink versus 100PLUS(TM) hydration bar as a pre-cooling strategy on 5 kilometre endurance run in male athletes - Muhammad Nizal Bin Razali (Nanyang Technological University, 2022)
The purpose of the study was to investigate the possible ergogenic and physiological effects of 100PLUS hydration bar on 5 kilometre endurance run in males. 14 participants consumed either 1 100PLUS hydration bar ( − 4°C; ICE) or 7.5 g · kg − 1 of chilled 100PLUS drink ( 4°C; CON) and performed a 15-min warm-up before a 5km outdoor running time-trial. There was no significant difference in mean performance time between ICE (1474±116 s) and CON (1475±85 s; p=0.986) but 9 participants showed an improvement in performance. There was no significant difference in estimated core temperature (p=1.000) and heart rate (p=1.000) prior to the run between trials. There was a significant difference in estimated core temperature (p=0.026) and heart rate (p=0.047) during the run between ICE and CON. At the end of the time-trial, estimated core temperature (p<0.001) was higher in ICE (40.2±0.8°C) than CON (39.4±0.4°C) but heart rate showed no significant difference (p=1.000). Although one serving of hydration bar was not enough to lower the core temperature significantly, it was effective in reducing participant’s perception of thermoregulatory strain and increasing perceived effort to improve performance.